Optimization of Heat Treatment process and Quenching cycles for Hadfield steel - Alsebaie,Abdullah (2026)
Hadfield steel is widely used in heavy-duty applications involving high impact loads and abrasive wear, such as mining and stone crushing equipment, due to its high toughness, ductility, and work-hardening ability. However, the as-cast microstructure contains carbide precipitation and chemical segregation, particularly along grain boundaries, which causes embrittlement and reduce service performance. Therefore, proper heat treatment followed by rapid quenching is essential to dissolve carbides and retain fully austenitic microstructure. The aim of this thesis was to investigate and optimize heat treatment and quenching cycles for different Hadfield steel Grades, with focus on thermal gradients in thick sections, carbide dissolution, grain size, and hardness. Two steel Grades were studied, GRADE A and GRADE B, using different sample geometries. Thick blocks were used to study thermal gradients between the core and surface, where plate samples were used to compare different heat treatment cycles. The results showed significant differences between the surface and core temperature during the quenching, demonstrating the challenge of heat-treating thick Hadfield steel components due to the material’s poor thermal conductivity. Among the heat treatment cycles investigated, the temperature step-down method prior to quenching and the two-step heat treatment showed promising results of carbide-free microstructure while maintaining refined grain size. Overall, this thesis highlights the importance of optimizing the heat treatment and quenching parameters according to section thickness and chemical composition.
Keywords: Hadfield Steel; heat treatment; quenching; thermocouple.